Arsenic trioxide-based therapy of relapsed acute promyelocytic leukemia: registry results from the European LeukemiaNet - Lengfelder, Eva; Hofmann, Wolf-Karsten (Leukemia, 2015)
In 2008, a European registry of relapsed acute promyelocytic leukemia was established by the European LeukemiaNet. Outcome data were available for 155 patients treated with arsenic trioxide in first relapse. In hematological relapse (n=104), 91% of the patients entered complete hematological remission (CR), 7% had induction death and 2% resistance, 27% developed differentiation syndrome and 39% leukocytosis, whereas no death or side effects occurred in patients treated in molecular relapse (n=40). The rate of molecular (m)CR was 74% in hematological and 62% in molecular relapse (P=0.3). All patients with extramedullary relapse (n=11) entered clinical and mCR. After 3.2 years median follow-up, the 3-year overall survival (OS) and cumulative incidence of second relapse were 68% and 41% in hematological relapse, 66% and 48% in molecular relapse and 90 and 11% in extramedullary relapse, respectively. After allogeneic or autologous transplantation in second CR (n=93), the 3-year OS was 80% compared with 59% without transplantation (n=55) (P=0.03). Multivariable analysis demonstrated the favorable prognostic impact of first remission duration ⩾1.5 years, achievement of mCR and allogeneic or autologous transplantation on OS of patients alive after induction (P=0.03, P=0.01, P=0.01) and on leukemia-free survival (P=0.006, P<0.0001, P=0.003), respectively.